From pages to places: portrayals of environmental challenges in Vietnamese children’s picture storybooks - Phung,Nguyen Anh (Master Thesis Series in Environmental Studies and Sustainability Science, 2025)
The use of picture storybooks has the potential to foster children’s environmental awareness and promote behavioural change, but little is known about their connection to the local context, particularly in Vietnam. This thesis presents a qualitative content analysis of sixteen children’s picture storybooks with environmental themes written by Vietnamese authors and illustrators, examining how they portray environmental challenges and their solutions. The analysis is based on the biophysical, psychological, sociocultural and political economic dimensions of the place-based education framework. The results show that while several picture storybooks effectively support place-based education, others still rely on generalised contexts with limited local relevance. Given the importance of place in strengthening children’s emotional connection and responsibility toward their communities, these insights highlight future opportunities for authors, illustrators, and publishers to produce more locally grounded environmental picture storybooks in Vietnam.
Keywords: Sustainability Science; picture book; place-based education; qualitative content analysis; Vietnam